National Recovery and Resilience Plan: Latvia - Romele, Linda (Italian Labour Law e-Journal, 2022)
Political leaders and civil society representatives, including the social partners, reached agreement on the main elements to be incorporated in Latvia’s Recovery and Resilience Plan (RRP). The social partners, however, are not entirely satisfied with the final result. Among other things, they regard it as too fragmented and lacking ambition. Both social and cooperating partners, such as the Free Trade Union Confederation of Latvia, the Employers’ Confederation of Latvia and the Latvian Chamber of Commerce and Industry, were brought on board too late, practically when the plan was ready and was about to be approved by the Cabinet of Ministers. The positive thing is the fact that the RRP for each EU Member State had to be prepared based on the recommendations of the European Commission within the framework of the European Semester. While hitherto EC recommendations were merely suggested, their integration in the economic recovery strategy has increased their impact. Moreover, unlike EU Structural Fund financing, the EU financial assistance of the RRF can be directed only to areas in which reforms are planned within the framework of the RRP, with a specific focus on the green transition.